Cuprous ions embedded in ceria lattice for selective and stable electrochemical reduction of carbon dioxide to ethylene. Issue 20 (8th May 2018) - Wu, Di; Dong, Cunku; Wu, Deyao; Fu, Jianyu; Liu, Hui; Hu, Shanwei; Jiang, Zheng; Qiao, Shi Zhang; Du, Xi-Wen
Abstract : Cuprous ions incorporated into a ceria lattice for electrochemical reduction of CO2 to ethylene with excellent selectivity and stability. Abstract : Electrochemical reduction of carbon dioxide (CO2 ) shows high potential to remedy greenhouse gas emission and over-dependence on fossil fuels; nevertheless, it remains a big challenge to selectively reduce CO2 to a hydrocarbon fuel with high energy density. Here we report a novel electrocatalyst, ceria doped with cuprous ions, which can produce ethylene selectively and stably; specifically, the faradaic efficiency for ethylene reaches 47.6% at −1.1 V vs. RHE, and the high current density is maintained steadily for several hours. The active sites are experimentally identified as cuprous ions which are stabilized by ceria and responsible for long term durability. Furthermore, theoretical calculations indicate that cuprous ions favor C–C coupling and thus have high selectivity to ethylene. Our work demonstrates that doping an inert substrate with active ions is an effective way to improve the selectivity and stability of catalysis, which promises high yield of hydrocarbon fuels.